Rationale for the Grip of Fertilizer Application Machines (The Peerian Journal, 2023)
An analysis of the influence of the working width of MTA for the application of mineral fertilizers on the quality of distribution of ammophos and potassium chloride on the unevenness of the distribution of mineral fertilizers was carried out. As a result of static processing of the results obtained, the regularity of the change in the unevenness index depending on the working width of the unit was established.